(untitled) (Conferencea, 2022)
Challenging yet pleasurable communicative approach promotes positive attitude toward the daily study in language learning. Pupils working in groups have comprehension activity, journal sharing, question discussion and role-playing of the characters in the books or plays. Communicative approach not only lightens classroom anxiety but also promotes pupils cooperative learning and enhances their communication abilities.